Symbolic Imagery and the Realm of Psyche - Schwartz, Susan L (Journal of Dharma, 1984)
When psychology takes up the study of religious imagery it engages in the quest for meaning; in this the psychologist differs little from those whose interest is rooted in faith or scholarship. Indeed, psychology has as its etymological root psyche, that is, soul, whose nature has been the focus of religious traditions from time immemorial. That religion and psychology have often been at odds is no coincidence, for they lay claim to the same territory: the relationship between the human soul and its experience in the world. The development of awareness is sought by bbth. The act of transformation spiritual, psychological and even physical, is at the centre of both religion and psychology. Thus the role of symbols as images leading towards transformatiÓn is as essential to analytical psychology as it is to the sacred traditions.